Discretion and Diversion in Albany’s Lead Program - Worden, Robert E. (Criminal justice policy review, 2018)
In early 2016, Albany police launched its law-enforcement-assisted diversion (LEAD) program, providing for discretionary prebooking diversion for low-level offenders whose offending was driven by drug addiction, mental illness, homelessness, or poverty. We examine the exercise of officers’ discretion in making LEAD diversions by analyzing eligible incidents to estimate the effects of offense-, suspect-, and officer-related variables on discretionary decisions, and by analyzing semistructured interviews with officers. We find that in the first year of LEAD, diversions were few in number, and the individuals diverted to LEAD were not generally people with a high level of previous justice involvement. Officers’ attitudes toward diversion and toward LEAD were mixed, and those attitudes influenced the exercise of their discretion. Overall, we find evidence of the same kinds of challenges that have confronted the implementation of new programs in many police agencies, particularly challenges to “pluralized” drug control.